The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jsbm.12291
|View full text |Cite
|
Sign up to set email alerts
|

Entry Mode Research and SMEs: A Review and Future Research Agenda

Abstract: Research on SMEs' entry modes remains limited and is spread across various, often disconnected research fields using a broad variety of theories, sample characteristics, and methods. This makes it challenging for researchers to identify interesting research opportunities. Our study investigates the current state of the SME entry mode literature by conducting a systematic literature review of 47 articles. Our review shows that scholars should be more careful when conceptualizing SMEs, and we recommend the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 100 publications
(195 reference statements)
0
46
0
Order By: Relevance
“…The process of internationalization for small and medium‐sized enterprises (SMEs) has attracted increasing attention from Entrepreneurship literature (Bruneel and De Cock ; Kuivalainen et al ; McAuley ). This is not surprising, considering that in the current “globalized” environment, many SMEs are rapidly accessing international markets (European Commission ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The process of internationalization for small and medium‐sized enterprises (SMEs) has attracted increasing attention from Entrepreneurship literature (Bruneel and De Cock ; Kuivalainen et al ; McAuley ). This is not surprising, considering that in the current “globalized” environment, many SMEs are rapidly accessing international markets (European Commission ).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have emphasized that social networks are crucial for SMEs since in such firms, many decisions, including those concerning international growth, often depend upon a single person, with her capital of knowledge, experience, and, crucially, relationships. Among other webs of ties, entrepreneurs’ networks are particularly critical because the entrepreneurs in small firms have greater discretion to make decisions and more frequently perform key boundary‐spanning roles (Bruneel and De Cock ; Holmlund and Kock ; Jones and Coviello ). Scholars have also highlighted that social networks are important not only in the pre‐entry phase, but also in the subsequent moments of international strategies, where they play different roles (Agndal, Chetty, and Wilson ; Chetty and Agndal ; Lindstrand, Melén, and Nordman ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transaction cost theory is the most frequently used theoretical perspective, followed by OLI and resource-based view [10]. Studies applying transaction cost theory have shown the importance of environmental uncertainty and asset specificity, and have found that: when the environmental uncertainty is high, firms are more likely to adopt non-equity entry modes [11]; firms with high asset specificity tend to prefer entry mode with high control [12]; firms will choose high-control entry mode when both of them are high [13].…”
Section: B Recent Researchmentioning
confidence: 99%